SMACing the bank : how to use social media, mobility, analytics and cloud technologies to transform the business processes of banks and the banking experience /: how to use social media, mobility, analytics and cloud technologies to transform the business processes of banks and the banking experience. ([2018]) - Raghunathan, Balaji; Maiya, Rajashekara
No abstract available